Electron microscopic study of adrenal glands of rats in the early stages after thermal burn - Pastukhova , V.A.; Lukyantseva , H.V.; Tуtarenko , V.M. (Морфологія / Morphologia / Morfologìâ, 2023)
Background of the problem of thermal injuries is determined by the relatively high frequency of their occurrence in domestic and industrial conditions, the severity of burn injury, the complexity and duration of treatment of patients with burns, a sharp decrease in the quality of life, frequent disability and high mortality. Objective is to investigate the changes in the medulla of the adrenal glands of rats in the early stages after a thermal burn at the electron microscopic level. Methods. The study was conducted on white rats of reproductive age, which were simulated thermal skin burn. Pieces of adrenal glands were processed according to the generally accepted method, ultrathin sections were made, which were then examined and photographed under an electron microscope. Results. On the 1st day of observation, the integrity of the wall of the sinusoidal hemocapillaries was not disturbed. The endothelium was characterized by local swelling of the cytoplasm. Endotheliocytes were characterized by a relatively intact ultrastructure of the nucleus, but regression of the number of organelles was noted in the cytoplasm. On the 3rd day after the burn, the products of autolysis of cells were recorded in the lumen of some hemocapillaries, which indicates the development of dystrophic changes against the background of the burn, violation of the integrity of blood vessels. The thickness of the peripheral zone of the endothelium of hemocapillaries tended to decrease, i.e. signs of regression of hydropic dystrophy of endotheliocytes were noted. Endocrinocytes with pronounced swelling and reduction of organelles, primarily mitochondria, were recorded around affected and stagnant vessels. During the period of 7-14 days of observation, a state of synthetic exhaustion of endocrinocytes was established, as evidenced by the sharp degranulation of a significant number of epi- and norepinephric cells. Microcirculatory changes were morphologically manifested by swelling of the endothelium of hemocapillaries and, as a result, disorganization of perivascular endocrinocytes with the development of dystrophic disorders. Against the background of disorders of regional hemodynamics and energy deficit, apoptosis of individual endocrine cells was noted. Only individual elements of the endoplasmic reticulum and vesicles are observed. Endocrine activity of epinephrocytes was characterized by sharp activation of synthesis. Conclusion. Functional and morphological disorders develop in the medulla of rat adrenal glands after a thermal burn, which lead to dystrophy of the structural components of the gland. Functional changes at the level of microcirculation and secretory activity are noted on the 3rd day, dystrophic processes are registered on the 7th day and progress during the following observation periods.